Functional Carbazole‐Fullerene Complexes: A New Perspective of Carbazoles Acting as Nano‐Octopus to Capture Globular Fullerenes. Issue 40 (4th June 2021) - Liu, Xitong; Wang, Wei; Fan, Zhenqiang; Huang, Wanning; Luo, Lixing; Yang, Canglei; Zhang, Jing; Zhao, Jianfeng; Zhang, Lei; Huang, Wei
Abstract: Fullerene host‐guest constructs have attracted increasing attention owing to their molecular‐level hybrid arrangements. However, the usage of simple carbazolic derivatives to bind with fullerenes is rare. In this research, three novel carbazolic derivatives, containing a tunable bridging linker and carbazole units for the capturing of fullerenes, are rationally designed. Unlike the general concave‐convex interactions, fullerenes could interact with the planar carbazole subunits to form 2‐dimensional hexagonal/quadrilateral cocrystals with alternating stacking patterns of 1 : 1 or 1 : 2 stoichiometry, as well as the controllable fullerene packing modes. At the meanwhile, good electron‐transporting performances and significant photovoltaic effects were realized when a continuous C60⋅⋅⋅ C60 interaction channel existed. The results indicate that the introduction of such carbazolic system into fullerene receptor would provide new insights into novel fullerene host‐guest architectures for versatile applications. Abstract : A series of carbazolic derivatives are reported to associate with fullerenes as a novel host class. Different amounts of carbazole units and tunable bridged linker modulated the binding strength and its alternated arrangement pattern. Benefit from the continuous C60⋅⋅⋅ C60 short‐contact channels, promising electron‐transport and photovoltaic effects are achieved in the host‐guest complex devices.